2019
DOI: 10.1044/2019_jslhr-s-19-0018
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correlates of Fluent and Stuttered Speech Production in Preschool Children Who Stutter

Abstract: Purpose The purpose of this study was to compare physiological indices of sympathetic nervous system arousal recorded during fluent and stuttered utterances in a preschool children who stutter (CWS). Method Twenty-two 4- to 5-year-old CWS participated in the experiment. We recorded children's skin conductance response amplitude and frequency, blood pulse volume amplitude, and pulse rate as they completed a picture description task. We then compared indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…We did observe significantly higher background, tonic SCLs in CWS, on average, but these were not exclusive to speech production tasks. It is important to reiterate that the present results were derived from fluent intervals of speech, and SNS correlates of stuttering behaviors are reported in a companion paper (Walsh and Usler, in press).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We did observe significantly higher background, tonic SCLs in CWS, on average, but these were not exclusive to speech production tasks. It is important to reiterate that the present results were derived from fluent intervals of speech, and SNS correlates of stuttering behaviors are reported in a companion paper (Walsh and Usler, in press).…”
Section: Discussionmentioning
confidence: 70%
“…One hypothesis to consider is that speech specific increases in SNS activity develops later in CWS and/or that speech-specific phasic increases in SNS arousal would more likely be observed surrounding stuttering events. We addressed the latter hypothesis in a companion study (Walsh and Usler, in press). We found that stuttered utterances produced during a picture description task by CWS were associated with significantly higher phasic SCR amplitude, SCR frequency, and reduced BPV compared to fluent utterances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychophysiological research with children who stutter is somewhat limited. However, recently a number of studies have examined CWS's autonomic nervous system response to such speaking conditions as picture naming, picture description, and non-word repetition (Jones et al, 2014 , 2017 ; Zengin-Bolatkale et al, 2015 , 2018 ; Choi et al, 2016 ; Tumanova and Backes, 2019 ; Walsh and Usler, 2019 ; Walsh et al, 2019 ). Results of these studies generally indicate that CWS do not have an elevated level of autonomic arousal during speaking.…”
Section: Electrodermal Activity As a Measure Of Emotional Reactivitymentioning
confidence: 99%
“…Literature from speech science generally indicates that preschool-age children who stutter do not have an elevated autonomic arousal during such speaking tasks as picture naming, picture description, and non-word repetition [ 7 , 18 , 36 , 37 , 42 , 72 , 78 , 79 , 89 , 90 ]. However, differences in autonomic arousal between children who do and do not stutter based on the children’s age [ 89 ] and complexity of the speaking task [ 72 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%